Electromagnetic fields produced by incubators influence heart rate variability in newborns. Issue 4 (1st May 2008) - Bellieni, C V; Acampa, M; Maffei, M; Maffei, S; Perrone, S; Pinto, I; Stacchini, N; Buonocore, G
Abstract : Background: Incubators are largely used to preserve preterm and sick babies from postnatal stressors, but their motors produce high electromagnetic fields (EMFs). Newborns are chronically exposed to these EMFs, but no studies about their effects on the fragile developing neonatal structure exist. Aim: To verify whether the exposure to incubator motor electric power may alter autonomous nervous system activity in newborns. Material and methods: Heart rate variability (HRV) of 43 newborns in incubators was studied. The study group comprised 27 newborns whose HRV was studied throughout three 5-minute periods: with incubator motor on, off, and on again, respectively. Mean HRV values obtained during each period were compared. The control group comprised 16 newborns with constantly unrecordable EMF and exposed to changes in background noise, similar to those provoked by the incubator motor. Results: Mean (SD) total power and the high-frequency (HF) component of HRV increased significantly (from 87.1 (76.2) ms2 to 183.6 (168.5) ms2 ) and the mean low-frequency (LF)/HF ratio decreased significantly (from 2.0 (0.5) to 1.5 (0.6)) when the incubator motor was turned off. Basal values (HF = 107.1 (118.1) ms2 and LF/HF = 1.9 (0.6)) were restored when incubators were turned on again. The LF spectral component of HRV showed a statistically significant change only in the second phase of the experiment. Changes in background noise did not provoke any significant change in HRV. Conclusion: EMFs produced by incubators influence newborns' HRV, showing an influence on their autonomous nervous system. More research is needed to assess possible long-term consequences, since premature newborns may be exposed to these high EMFs for months.